P142 Does the appearance of the chest radiograph matter in pleural infection?. (12th November 2019) - Bedawi, EO; Kanellakis, NI; Kim, A; Pattabi, AL; Dudina, A; Mercer, RM; George, V; Rahman, NM; Hallifax, RJ
Abstract : Introduction: The chest radiograph is used in clinical practice to guide decision-making in the treatment of pleural infection. This outcome was used as the primary endpoint in the randomised second Multicentre Intrapleural Sepsis Trial (MIST-2), defined as the change in area of pleural opacity, measured as the percentage of the ipsilateral hemithorax occupied by effusion, from day 1 to day 7 [1]. The value of this radiographic outcome measure as a surrogate for predicting clinically important outcomes, e.g. time in hospital (LOS), surgery at 3 months and 3-month mortality, has not been directly addressed. Methods: Retrospective analyses were conducted using the prospectively collected data from the MIST-2 database (n=210). Regression analyses were modelled with number of days in hospital (linear), and surgery or death at 3 months, both individually and as a combined outcome (yes/no; logistic), as dependent variables. The independent variables were absolute change in chest radiograph opacity (MIST-2 primary endpoint) and relative change, which is more clinically applicable in daily practice (a secondary endpoint in MIST-2). Each of the analyses was corrected for day 1 radiograph appearance to account for baseline variability. SPSS v25 was used for all analyses. Results: Absolute and relative change in chest radiograph opacity were associated with hospital LOS and either surgery or death at 3 months (combined outcome) with strong statistical significance (p≤0.01). Analysing the components of the combined outcome individually, absolute and relative change were associated with surgery at 3 months (p≤0.01 and p=0.021 respectively). Absolute and relative change in chest radiograph to death at 3 months alone was borderline significant (p=0.089) and non-significant (p=0.16) respectively. Conclusion: These findings demonstrate that change in chest radiograph during the course of treatment of pleural infection is a robust and clinically important surrogate endpoint which appears to predict meaningful outcomes. Although surgery may be decided upon solely on the basis of the radiograph (which would explain this result), change in x-ray appearance predicts other important outcomes (length of stay). This data supports its clinical utility, and suggests its robust use as a research outcome measure.